SETTLEMENT – A mediator’s prayer - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2014)
In the post on the Kluwer Mediation Blog, the first published poetic piece on mediation ‘A Mediator’s Prayer’ by Hong Hong mediator, lawyer and poet, TK Iu, is applauded.